Tax-Motivated Trading by Individual Investors - Ivković, Zoran; Poterba, James; Weisbenner, Scott (American Economic Review, 2005)
We analyze stock trades made by individuals holding stock in both taxable and tax-deferred accounts. By comparing trades across these two types of accounts, we uncover a capital gains lock-in effect in taxable accounts. The lock-in effect is more pronounced for large stock transactions and for stocks held for at least 12 months. Over shorter horizons, the disposition effect outweighs the lock-in effect. Comparison of loss realizations in taxable and tax-deferred accounts yields evidence of tax-loss selling throughout the year. Effective accrual tax rates for stocks that experience substantial appreciation are substantially below the statutory tax rate on long-term gains.